Differential regulation of nitric oxide synthase function in aorta and tail artery from 5/6 nephrectomized rats. Issue 6 (5th November 2013) - Spradley, Frank T.; White, John J.; Paulson, William D.; Pollock, David M.; Pollock, Jennifer S.
Abstract: Chronic renal failure (CRF) is associated with hypertension and concomitant endothelial dysfunction, enhanced vasoconstriction, and nitric oxide synthase (NOS) dysfunction. Vascular function in patients is assessed in peripheral extremity arteries like the finger arteries, whereas animal studies often use the centrally located aorta. Therefore, we examined whether peripheral tail artery and aortic NOS function are differentially regulated by blood pressure in rats with CRF. Using wire myography, arterial function was assessed in 16‐week‐old Sprague‐Dawley rats that were subjected to 5/6 nephrectomy (Nx; arterial ligation model) 8 weeks earlier or non‐Nx (control) rats. In aortas from Nx rats, endothelial‐dependent vasorelaxation response to acetylcholine (ACh) was blunted and there was enhancement of phenylephrine (PE)‐mediated vasoconstriction. Inversely, tail arteries from Nx rats had no change in endothelial function and reduced response to PE. Studies where arterial segments were incubated with the nonspecific NOS inhibitor, L‐NAME, showed that Nx reduced NOS function in the aorta but increased NOS function in tail artery for both ACh and PE responses. Furthermore, the observed alterations in NOS function in both aorta and tail artery were abolished when mean arterial blood pressure, as assessed by telemetry, was maintained at normal levels in the 5/6 Nx rats using triple therapy: hydralazine (30 mg/kg per day), hydrochlorothiazide (10 mg/kg per day), and reserpine (0.5 mg/kg per day). In conclusion, differential changes of NOS function in central versus peripheral arteries in CRF are dependent upon hypertension. Abstract : e00145 Vascular function in renal failure patients is typically assessed in peripheral arteries like the brachial artery, whereas animal studies often use the centrally located aorta. We examined whether peripheral tail artery and aortic nitric oxide synthase (NOS) function are differentially regulated by blood pressure in rats with chronic renal failure. NOS inhibition showed that renal failure reduced and increased NOS function in aorta and tail artery, respectively, for both vasorelaxation and vasoconstriction responses. These alterations were abolished when blood pressure was normalized.